Respostas

2014-07-24T17:45:30-03:00
∆ = b²-4ac
∆ = (-6)² - 4 . 2 . (-56)
∆ = 36 - 448
∆  = 484

x = - b ± √ ∆ / 2.a
x = 6 +- 22 / 2.2
X¹ = 6 + 22 / 4 = 7
X² = 6 - 22 / 4 = -4
2 5 2
2014-07-24T17:49:35-03:00
A= 2    b= -6    c= -56

Δ= b²-4.a.c
Δ= -6²-4.2.(-56)
Δ= 36 + 448
Δ= 484

x'= -(-6) + √484    ------------> 6 + 22 --------------> 28  -------> 7
        2. 2                                   4                             4

x''= -(-6) - √484    ----------> 6 - 22 ------------> -16 ---------> -4
           2.2                                4                        4


Resultado: x'= 7 e x'' = -4
1 5 1